Development of an in situ injectable hydrogel containing hyaluronic acid for neural regeneration - Nguyen, LTB; Hsu, C-C; Ye, H; Cui, ZF (IOP Publishing, 2020)
In this work, a novel enzymatically crosslinked injectable hydrogel comprising hyaluronic acid (HyA), dopamine (DA), and 3-(4-Hydroxyphenyl) propionic acid (HPA) conjugates was successfully developed. To the best of our knowledge, it is the first time that HPA is conjugated to a HyA-based backbone. In situ hydrogelation of HyA-DA-HPA occurred in the presence of hydrogen peroxide (H2O2) as an oxidant and horseradish peroxidase (HRP) as a catalyst. Proton nuclear magnetic resonance and Fourier transform infrared spectroscopy were used to characterize the chemical reactions between HyA, DA, and HPA. Gel formation completed between 3 s to 5 min depending on the concentrations of polymer, HRP, and H2O2. Crosslinked HyA-DA-HPA gels acquired storage moduli ranging from ~100 Pa to ~20000 Pa (at f = 2000 rad/s). Biocompatibility of the hydrogels was examined with human mesenchymal stem cells (hMSCs) and human induced pluripotent stem cell-derived neural stem cells. The hydrogels made of 2.0 w/v % HyA-DA-HPA hydrogels, 0.24 U/mL HRP and ≤ 0.5 µmol/mL H2O2 were found biocompatible with hMSCs cultured on and encapsulated within the hydrogels. Since HyA serves as a backbone of the extracellular matrix in the central nervous system (CNS) and DA acquires the ability to restore dopaminergic neurons, use of this injectable HyA-DA-HPA hydrogel for stem cell transplantation is a potential treatment strategy for CNS repair and regeneration.